Food security and climate change: Challenges to 2050 and beyond - Nelson, Gerald C.; Rosegrant, Mark W.; Palazzo, Amanda; Gray, Ian; Ingersoll, Christina; Robertson, Richard D.; Tokgoz, Simla; Zhu, Tingju; Sulser, Timothy B.; Ringler, Claudia; Msangi, Siwa; You, Liangzhi (International Food Policy Research Institute, 2010)
The first decade of the 21st century has brought harbingers of a troubled future for global food security. The food-price spike of 2008 led to food riots and political change in several countries. In 2010, the excessive heat and drought in Russia that led to wildfires and a grain embargo, as well as the unprecedented floods in Pakistan, signal more trouble ahead. A world population approaching 9 billion by 2050 and higher incomes in hitherto poor countries will lead to increased food demand, which means significant challenges to sustainable agricultural production.